Significados del bachillerato en jóvenes de colonias periurbanas marginadas en Yucatán, México - Heredia Soberanis, Norma Graciella (Universidad de Costa Rica, 2020)
This article reports the findings of an research carried out with students from a context of socio-economic and cultural disadvantage of marginalized colonies in Yucatan Mexico, given the social relevance of studying a baccalaureate in order to obtain employment or continue higher education; the objective was to explore various meanings and senses with regard to studying, remaining in and completing higher secondary education, based on the school experience of young people from a General Community High School. The type of research is a case study with a qualitative focus; 27 students participated as key informants: 23 in two focus groups and 4 in individual interviews; the methodology for analyzing the data consisted of sociological analysis of the speeches. As a result it was found that the high school acquires the meaning of an instrument to achieve personal improvement and economic and intellectual progress in the future. Referring to the distributive dimension of social justice: having a good job and a good salary are factors perceived as necessary to achieve social recognition, so that education is seen as a valid and legitimate instrument to obtain them, ideologically constituting an instrument of social struggle of young people in socioeconomic and cultural disadvantage, for the achievement of a hegemonic model of adult life, presenting a masked individualism of solidarity liberation. There is evidence of the representation of notions of social and educational justice that normalize the unequal redistribution of goods and services, the lack of social recognition of vulnerable groups, and the emphasis on neoliberal consumption.